(3GdbjGOI hGdQbGHI hGdGJUGd GdEOGQj (B/s - (3YjGUQI, eYf eMehOs; (3Hfj CMeO, eQhGf eMeOs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2015)
(3jJfGhd eONd Edi Yde GdGOGQI, GdhXGFa GdGOGQjI, GdQbGHI GdGOGQjI, GdeSGAdI, GdJbhje, GJNGP GdbQGQGJ, GdbjGOI GdEOGQjI, GdGJUGds
(3HHdjhZQGajG(B: 183-188s
Keywords: (3GdGJUGds; (3GdbjGOI GdEOGQjIs